MRI staging of colorectal cancer (2016)
Colorectal cancer is the fourth leading cause of death worldwide and the fifth leading cause of cancer death in Colombia. MRIs are ideal for evaluating colorectal cancer, especially for screening, because they allow staging by determining the extent of any invasion beyond the muscularis and into adjacent organs. This is key for identifying candidates for chemotherapy and/or preoperative radiation therapy and for planning surgical procedures. The key is differentiation between stages T2 and T3 by using T2 sequences with high resolution information. In addition, MRIs allow assessment of the size and morphology of the lymph nodes and greatly increases the specificity of detection of nodal involvement. Magnetic resonance imaging has high specificity and reproducibility. © 2016 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.